Organizational Performance and Technology Innovation on Globalization Project - John Daniel, Mikel; Osuma Telmon, Iskoraria (International Journal of Economics and Business Management, 2025)
This study looks at how globalization affects how projects are delivered and how well organizations perform. Globalization is a complex idea that has both good and bad sides, as well as opportunities and challenges. The study aims to understand how opening up economies and technological advances impact project delivery and how organizations operate. It is an actual research study that uses surveys to gather and organize information from 90 people who are representative of the population. The data is analyzed using statistical methods with the help of SPSS software. The results show that the original ideas, or null hypotheses, were not supported, and the alternative ideas were accepted. Based on the results, the study suggests that countries should open up their economies and reduce trade barriers to help companies become more productive and efficient. Also, managers should create strategies that meet customer needs in order to stay competitive in the market